LAD-1/variant syndrome is caused by mutations in FERMT3 - Kuijpers, Taco W; van de Vijver, Edith; Weterman, Marian A J; de Boer, Martin; Tool, Anton T J; van den Berg, Timo K; Moser, Markus; Jakobs, Marja E; Seeger, Karl; Sanal, Ozden; Unal, Sule; Cetin, Mualla; et al. (Blood, 2009)
Leukocyte adhesion deficiency-1/variant (LAD1v) syndrome presents early in life and manifests by infections without pus formation in the presence of a leukocytosis combined with a Glanzmann-type bleeding disorder, resulting from a hematopoietic defect in integrin activation. In 7 consanguineous families, we previously established that this defect was not the result of defective Rap1 activation, as proposed by other investigators. In search of the genetic defect, we carried out homozygosity mapping in 3 of these patients, and a 13-Mb region on chromosome 11 was identified. All 7 LAD1v families share the same haplotype, in which 3 disease-associated sequence variants were identified: a putative splice site mutation in CALDAGGEF1 (encoding an exchange factor for Rap1), an intronic 1.8-kb deletion in NRXN2, and a premature stop codon (p.Arg509X) in FERMT3. Two other LAD1v patients were found to carry different stop codons in FERMT3 (p.Arg573X and p.Trp229X) and lacked the CALDAGGEF1 and NRXN2 mutations, providing convincing evidence that FERMT3 is the gene responsible for LAD1v. FERMT3 encodes kindlin-3 in hematopoietic cells, a protein present together with integrins in focal adhesions. Kindlin-3 protein expression was undetectable in the leukocytes and platelets of all patients tested. These results indicate that the LAD1v syndrome is caused by truncating mutations in FERMT3.